Characteristics and clinical outcomes for mental health patients admitted to a behavioural assessment unit: Implications for model of care and practice. (14th September 2020) - Daniel, Catherine; Mukaro, Violet; Yap, Celene Y. L.; C Knott, Jonathan; Kelly, Peter; Innes, Andrew; Braitberg, George; Gerdtz, Marie
Abstract: Behavioural assessment units (BAU) have been established in emergency departments (EDs) to provide short‐term observation, treatment, and care to people experiencing acute behavioural disturbance. A prospective observational study was conducted in a cohort of adult patients admitted to one BAU located within an ED (July–December 2017) to compare clinical characteristics, treatment outcomes, and use of restrictive interventions for those who received a specialist mental health (MH) assessment with those who did not. Of the 457 patients, 61.5% received a specialist MH assessment. This group had a lower acuity (Australasian Triage Score 10.4%; CI 0.2–2.0% vs 13.6%; CI 9.3–19.5%); more arrived with police (28.8%; CI 23.8–34.3 vs 5.1%; CI 2.7–9.4%); and were subjected to restrictive interventions while in the BAU. Security responses for unarmed threat (code grey) were higher (10.9%; CI 7.8–15.0% vs 4.4%; CI 2.3–8.5%), as was the use of chemical restraint (4.2%; CI 2.4–7.2 vs 0.0% CI 0.0 – 2.1%). Those requiring specialist MH assessment had a longer length of stay (12.7 vs 5.2 hours). Further development of the BAU model of care must include targeted, evidence‐based strategies to minimize the use of restrictive interventions and ensure timely access to acute mental health services.